Exciton migration in self-assembled dendrite-type fractal superstructures of monodisperse Quantum Dots - Bernardo, César (2014)
We investigated dendrite shaped superstructures made of two different QDs, namely CdSe/ZnS and CdTe. Due to the dense packing of QDs, Förster resonance energy transfer (FRET) may compete with deexcitation, and the specific dendrite shaped structure suggests the possibility of funneling of excitation from the edges of the structure to the center.